HUBUNGAN PERILAKU PICKY EATER DENGAN TINGKAT KECUKUPAN ZAT GIZI PADA ANAK AUTISM SPEKTRUM DISORDER (ASD)[Correlation between Picky Eater Behavior and Nutrient Adequacy of Children with Autism Spektrum Disorder (ASD] - Nelsa Kurnia; Lailatul Muniroh (Media Gizi Indonesia, 2018)
Parents of children with Autism Spectrum Disorder (ASD) often report that their children are picky eater or selective in consuming food and refuse to try new food. This may affect the adequacy of nutritional intake. The purpose of this research was to analyse the correlation between picky eater behavior and nutrient adequacy of children with autism. This cross sectional research was conducted in 38 children with autism at SLB AGCA Center Surabaya using random sampling technique. The correlation between picky eater behavior and nutrient adequacy was analyzed by Chisquare. Based on the result of this research, there was correlation between picky eater behavior and energy adequacy (p=0.007), calcium (p =0.002) and zinc (p=0.010). On the other hand, there was no correlation between picky eater behavior and protein adequacy. It is suggested that parents should increase food intake of children with picky eater behavior, especially food that contain energy, calcium and zinc. Parents should try to offer new food, so the children wants to eat.